Factors Affecting Sustainability Report Disclosure in Indonesia (Survey of companies participating in ASRRAT 2022-2023) - Pulungan, M Alif Al Ghifari; Safelia, Nela; Ridwan, Muhammad (Asian Journal of Management Analytics, 2025)
The purpose of this study is to examine the Factors Affecting Sustainability Report Disclosure in Indonesia (Survey of companies participating in ASSRAT 2022-2023). By looking for sustainability and yearly reports on each company's website, this study leverages secondary data. Purposive sampling is the method of sampling that is employed. Over the course of two years, this study used a sample of seventeen companies, for a total of thirty-four companies. Multiple linear regression utilizing the SPSS version 25 data analysis tool is the data analysis technique employed in this investigation. The study's findings suggest that board size and leverage significantly impact the disclosure of sustainability reports. However, the disclosure of sustainability reports is not significantly impacted by a company's size, age, profitability, or liquidity.